Electrochemical Reduction of CO2 to Ethane through Stabilization of an Ethoxy Intermediate. (25th May 2020) - Vasileff, Anthony; Zhu, Yanping; Zhi, Xing; Zhao, Yongqiang; Ge, Lei; Chen, Hao Ming; Zheng, Yao; Qiao, Shi‐Zhang
Abstract: Electrochemical conversion of CO2 into ethane is seldom observed because of the generally higher selectivity towards methane, ethylene, and ethanol. Consequently, little experimental evidence for its reaction mechanism exists and thus remains largely unknown. Now, by combining electrochemistry with in situ X‐ray absorption fine‐structure and in situ Raman techniques, iodide‐derived copper (ID‐Cu) and oxide‐derived copper (OD‐Cu) systems were studied to obtain a deeper understanding of the CO2 to ethane mechanism. With trace iodine species on the surface and positively charged Cu species, production of ethane is significantly more favored on ID‐Cu compared to OD‐Cu, with higher selectivity and faster kinetics. For the first time, it is experimentally found that the formation of ethane follows the same pathway to ethylene and ethanol, and better stabilization of the late stage ethoxy intermediate can steer the reaction to ethane over ethanol. Abstract : Full reduction : In situ Raman and X‐ray absorption spectroscopy were combined with electrochemistry to study the relatively unknown CO2 reduction to ethane mechanism. A model iodide‐derived copper (ID‐Cu) catalyst was studied owing to its relatively high selectivity towards ethane compared to other systems. Trace iodine species and positively charged Cu species on ID‐Cu favored ethane production, which was shown to proceed via an ethoxy intermediate.